Pyramiding resistance genes to Fusarium head blight and rusts from Thinopyrum ponticum into durum wheat - Forte P.; Kuzmanović L.; Virili M. E.; Gennaro A.; Bitti A.; Ceoloni C. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Taking advantage of climate changes, unfamiliar pests and diseases are challenging wheat crop species. This is the case for Fusarium Head Blight (FHB), which has recently become a threat in unusual environments, including those where durum wheat is traditionally cultivated. Since currently available durum wheats are largely susceptible to FHB, new varieties are needed capable of maintaining yield capacity and grain quality under the disease pressure. A sustainable approach to achieve this aim is represented by transfer of resistance genes/QTL from related Triticeae species by means of “chromosome engineering”. We resorted to this cytogenetic strategy, efficiently complemented with advanced characterization and selection systems, to transfer into durum a gene/QTL for FHB resistance (provisional designation Fhb-7el2) located on the 7el2L arm of the wild Thinopyrum ponticum. A bread wheat 7DS.7el2L translocation line was employed as donor of the trait in crosses with previously developed durum wheat 7AS.7AL-7el1L recombinant genotypes, carrying additional resistance genes (Lr19+Sr25) deriving from a different Th. ponticum accession. Given the nearly complete homology between the 7el1L and 7el2L arms, and in spite of some pairing reduction in the pentaploid F1’s, pyramiding into durum of target genes/QTL from the two Th. ponticum accessions was successfully achieved. The selected multiple recombinant lines exhibited up to 80% reduction of susceptibility following Fusarium inoculation. The present proof of the Fhb-7el2 efficacy also in durum wheat opens the way for its straightforward breeding exploitation.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)